Geospatial Science and Point-of-Care Testing: Creating Solutions for Population Access, Emergencies, Outbreaks, and Disasters - Kost, Gerald J. (Frontiers in Public Health, 2019)
BACKGROUND. The objectives are: a) to understand how to use geospatial concepts when implementing point-of-care testing (POCT), b) to facilitate emergency, outbreak, and disaster preparedness in healthcare small-world networks, c) to enhance regional resilience by using POCT in tandem with geographic information systems (GISs) and other spatial tools, and d) to present a multidimensional value proposition for optimized care at points of need, adaptable and scalable for public health and medical response in limited-resource countries and other settings. CONTENT. Content comprises ten geospatial solutions: 1) small-world networks and regional topography; 2) space-time transformation, hubs, and asset mapping; 3) spatial care pathsTM; 4) GIS-POCT case studies; 5) isolation laboratories, diagnostics isolators, and mobile laboratories for highly infectious diseases; 6) alternate care facilities; 7) prehospital testing on ambulances; 8) connected POCT outside hospitals; 9) unmanned aerial vehicles (drones); and 10) geospatial policy—national POCT policy and guidelines, demographic care units, and geographic risk assessment. Visual logistics and literature analysis identify interrelationships of these geospatial and POCT principles. VALUE. Small-world networks and their connectivity facilitate efficient and effective placement of POCT for optimal response, rescue, diagnosis, and treatment. Spatial care pathsTM can speed transport from primary care to referral centers bypassing topographic bottlenecks, process gaps, and time-consuming interruptions. Use of regional GISs to position POCT close to where patients live can facilitate triage in primary care and decrease therapeutic turnaround time, thereby creating timeliness especially useful during acute illness, complex crises, and unexpected disasters. Isolation laboratories equipped with POCT help stop outbreaks and safely provide support for those critically ill with highly infectious diseases. POCT-enabled spatial grids can locate sentinel cases and establish geographic limits of epidemics for ring vaccination. IMPACT. Synthesis of geospatial concepts generates inherently optimal and logical placement of POCT not only in the physical and temporal sense, but also conceptually as the way to improve crisis response and spatial resilience. If public health professionals, geospatial scientists, and POCT specialists join efforts, new collaborative teamwork can create faster and higher impact response during disasters, complex crises, outbreaks, and epidemics, as well as more efficient primary, urgent, and emergency community care.